EVALUATION OF SAGITTAL SKELETAL DYSPLASIA BY 3 CEPHALOMETRIC ANALYSIS METHODS - Habib, Saba; Khan, Waqas Ahmad; Awaisi, Zubair Hassan; Malik, Amna (Medical Journal of South Punjab, 2024)
Objective: The study aimed to evaluate the reliability and validity of various skeletal analyses for identifying sagittal skeletal patterns.Methodology: Orthodontics department at Nishtar Institute of Dentistry, Multan. Sixty individuals aged 17 to 25 years, with skeletal Class I, II, and III patterns were enrolled. For inclusion in these classes patients had to meet specific criteria for the Beta angle along with one of two measurements: the ANB angle or the Wits appraisal. Results: In Class I, sensitivity values for ANB, Wits appraisal, Beta angle, AB plane angle, Downs angle of convexity, and W angle were 82.6%, 52.2%, 69.6%, 91.3%, 95.7%, and 52.2%, respectively, with positive predictive values of 45.2%, 37.5%, 51.6%, 51.2%, 51.2%, and 44.4%.Conclusion: The Down’s angle of convexity has been identified as the most reliable and valid indicator across all sagittal groups, with particular effectiveness in evaluating individuals with a Class I sagittal pattern. Meanwhile, the ANB angle and the AB angle serve as reliable indicators for assessing sagittal discrepancies, making them useful tools for identifying Class II and Class III sagittal patterns.